1989
DOI: 10.1016/0090-3019(89)90231-0
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical prophylaxis of venous thrombosis in patients undergoing craniotomy: A randomized trial

Abstract: A randomized, prospective clinical trial of 70 patients undergoing craniotomy was performed to compare and evaluate two forms of mechanical prophylaxis of deep vein thrombosis. Thirty-eight patients received antiembolism stockings, whereas 32 patients received external pneumatic compression. Prophylaxis was begun preoperatively and continued intraoperatively and post-operatively until the patients were ambulatory. Impedance plethysmography was used to detect deep vein thrombosis both preoperatively and postope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
3

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(25 citation statements)
references
References 20 publications
1
21
0
3
Order By: Relevance
“…Turpie et al [26] randomized patients (n = 239; 117 with brain tumors) to CS alone, CS in combination with ICD, or no prophylaxis and found a reduction in frequency of DVT from 20% in patients without prophylaxis to 9% in both treatment arms. Another randomized study [27] compared ICD with ICD + CS and found similar rates of DVT in 70 patients of whom 39 underwent surgery for brain neoplasm. In contradistinction to the two aforementioned studies, Wautrecht et al [28] randomized 23 patients undergoing surgery exclusively for brain tumors and reported that ICD + CS was superior to CS alone in decreasing the incidence of post-operative DVT (40% in the CS group vs. 0% with combined CS + ICD).…”
Section: Prophylaxis With Mechanical Devicesmentioning
confidence: 95%
“…Turpie et al [26] randomized patients (n = 239; 117 with brain tumors) to CS alone, CS in combination with ICD, or no prophylaxis and found a reduction in frequency of DVT from 20% in patients without prophylaxis to 9% in both treatment arms. Another randomized study [27] compared ICD with ICD + CS and found similar rates of DVT in 70 patients of whom 39 underwent surgery for brain neoplasm. In contradistinction to the two aforementioned studies, Wautrecht et al [28] randomized 23 patients undergoing surgery exclusively for brain tumors and reported that ICD + CS was superior to CS alone in decreasing the incidence of post-operative DVT (40% in the CS group vs. 0% with combined CS + ICD).…”
Section: Prophylaxis With Mechanical Devicesmentioning
confidence: 95%
“…), early ambulation, and medical treatment with various preparations of heparin, enoxaparin, or other anticoagulants [23][24][25][26][27][28]. In patients who have undergone resection of an intracranial lesion, many neurosurgeons remain reluctant to prescribe prophylactic anticoagulants due to the risk of post-operative intracranial hemorrhage [1,3,11,24,[29][30][31][32][33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…In 2 commonly cited series, patients received only leg wrapping and early ambulation for VTE prophylaxis. 7,8 In neurosurgical patients, the use of pneumatic compression devices has been shown to decrease VTE rates by up to 50%, 13,14 and low-dose heparin provides an additional 38% relative risk reduction.…”
Section: Discussionmentioning
confidence: 99%